Learning to See: Wittgenstein and Perception in Terrence Malick's The Thin Red Line - Roberts, Luke H. (The journal of religion and film, 2024)
This paper reflects on Ludwig Wittgenstein's influence on the work of filmmaker Terrence Malick. After calling attention to the connection between the American director and the Austrian philosopher, I note central components of Wittgenstein's philosophical aims, particularly highlighting his comments on "aspect change," his methodology of difficulty, and his linking of the ethical and aesthetic as "transcendental." With these insights in hand, and following recent scholarship on Malick's cinematic ethics, the paper examines Malick's 1998 film The Thin Red Line as an exemplary case for considering Malick as a filmmaker fundamentally concerned with ways of seeing the world. The analysis of this theme in the film centers on the alternative perspectives of Sergeant Welsh and Private Witt. In closing, this paper examines the ethical ends of these opposing visions and the way Malick's depiction of them allows one to see them as perspectives.